Food & beverage cost control - Dopson, Lea R.
"In order for foodservice managers to control costs effectively, they must have a firm grasp of accounting, marketing, and legal issues, as well as an understanding of food and beverage sanitation, production, and service methods. This fully updated sixth edition of Food and Beverage Cost Control provides students and managers with a wealth of comprehensive resources and the specific tools they need to keep costs low and profit margins high"--